Mechanical behaviours of a base course material in Western Australia - Chummuneerat, Suphat; Jitsangiam, Peerapong; Nikraz, Hamid (Australian Road Research Board (ARRB), 2012)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is produced by adding 2% Portland cement (by mass) to a standard crushed rock at an optimum moisture condition. The unique production process of HCTCRB different from that of a common cement treated base is the remixing process which is performed after the hydration of cement. This prevents cementitious bonding and maintains unbound material characteristics with an improvement in material engineering properties. This study aims to examine the resilient modulus (MR) and permanent deformation (PD) of HCTCRB under various conditions of water addition during compaction and dryback. The results indicate that the higher the moisture content of HCTCRB, the poorer the PD and MR performance. Higher addition of water during compaction causes the inferior PD and MR performance even though the samples achieved the higher dry density. The dryback process to achieve the dryer condition can improve the material performance. After the test specimens were subjected to the dryback process, it was found that the samples prepared by adding water during compaction resulted in poorer material performance in comparison to that of the samples that were compacted without additional water. Thus, the amounts of water added to mixes during compaction must be closely monitored.